Simultaneous desulfurization and magnetization in suspension roasting of high-sulfur and high-iron bauxite for aluminum–iron separation - Ruoxin Li; Chaoyi Chen; Junqi Li; Guoliang Wei; Xin Lin; Gangan Wang (Minerals Engineering, 2026)

A dual-channel hydrogel sensor for body temperature and exercise monitoring with simultaneous strain-temperature discrimination - Tiantian Wang; Jiayi Fu; Chengrui Jiang; Xun Wang; Panpan Shen; Fan Wang; Dehua Li; Ruoxin Li; Yi Hu; Guangtao Chang (Chemical Engineering Journal, 2026)

Multi-scale analysis of seed dormancy in Lonicera maackii and functional identification of LmABI5 in promoting dormancy - Ruoxin Duan; Ruofan Li; Jing Xu; Ran Zhao; Yanrui Ge; Yifan Liu; Ruili Li (Plant Science, 2026)

Industrial-scale processing of Enshi Yulu tea: Steam fixation as the critical step driving flavor formation - Mingjin Li; Yaowen Wan; Ruoxin Xu; Junfeng Jiang; Chenyang Liu; Qian Pu; Mengyuan Sui; Shuang Wu; Zizhen Qiao; Xingming Hu; Jun Xiang; Xiaoying Liu; et al. (Food Research International, 2026)

Machine learning paradigms in natural and engineered water systems: From proof-of-concept to trustworthy deployment - Ruoxin Ma; Jiqun Li; Zekun Zhang; Yunxian Liu; Hao Xu; Wei Yan (Water Research, 2026)

Design of dual-atom catalysts for CO2 reduction to C2 products: From synergistic mechanisms to machine learning guidance - Jiqun Li; Zekun Zhang; Ruoxin Ma; Luping Zhang; Xixue He; Wei Yan; Hao Xu (Chemical Engineering Journal, 2026)

Efficient phosphate removal and flocculation of Microcystis aeruginosa via a flower-like spherical Metal-Organic Framework La-BDC-NH2: Investigation of performance and mechanism - Jinyun Guan; Dandan Wang; Xiaozheng Ma; Ruoxin Wang; Lin Dang; Yihang Sun; Yichenyang Li; Jifeng Guo (Chemical Engineering Journal, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Carbon emission reduction of bike-sharing around the COVID-19 pandemic based on fine-grained recognition of riding activities - Rui Xin; Mengjie Gong; Jian Yang; Xinping Li; Bo Ai; Ruoxin Zhu (Journal of Cleaner Production, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

A review of curcumin-mediated photodynamic bactericidal technology for food preservation: Limitations and improvement strategies - Zhenlong Zhou; Pengzhen Li; Ruoxin Chen; Xinyu Cai; Wenjun Zhang; Penghui Fan; Jianyu Su (Food Microbiology, 2025)

Machine learning-based sweet spot prediction for lacuscrine shale oil in the Weixinan Sag, Beibu Gulf Basin, China - Ruoxin Huang; Yifan Li; Zhiqian Gao; Caiwei Fan; Junjun You; Ruisi Li; Chengkun Deng; Guocui Li (Marine and Petroleum Geology, 2025)

Brilliant fabrication of multifunctional collagen-based packaging films with rigid-flexible coupling structure bio-inspired by pangolins - Xiu Shi; Fengxian Ju; Ruoxin Wang; Jing Xu; Tianduo Li; Tao Wei; Aijie Lv; Huan Yang (Food Chemistry, 2025)

Energy transfer strategy inspired by TADF molecules for efficient and UV-Robust perovskite solar cells - Ping Hu; Liujiang Zhang; Ruoxin Yang; Rongen Guo; Xingyu Gao; Mingdeng Wei; Yafeng Li (Chemical Engineering Journal, 2025)

Natural borneol improves cellular uptake of curcumin to enhance its photodynamic bactericidal activity against Escherichia coli ATCC 8739 - Zhenlong Zhou; Ruoxin Chen; Pengzhen Li; Penghui Fan; Lin Ma; Xinyu Cai; Yuchao Hou; Binbin Li; Jianyu Su (Food Microbiology, 2025)

PVA/chitosan-based multifunctional hydrogels constructed through multi-bonding synergies and their application in flexible sensors - Tiantian Wang; Bingbing Xu; Tong Yu; Yan Yu; Jiayi Fu; Yuhang Wang; Xianwu Gao; Zhebin Xue; Ruoxin Li; Guangtao Chang (Carbohydrate Polymers, 2025)

Highly efficient reduction of Cr(VI) from industries sewage using novel biomass-driven carbon dots modified TiO2 under sunlight - Ruoxin Ma; Zijun Xu; Chun Zhang; Hao Li; Jiao Chen; Jingbiao Fan; Qingdong Shi (Chemical Engineering Journal, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Numerical simulation on the propulsion performance of a bioinspired swimmer with crescent-shaped caudal fin during accelerating and cruising motion - Qingyang Zhao; Ruoxin Li; Yuanchuan Liu; Chunyu Guo (Ocean Engineering, 2024)

Parametric analysis on the acoustic characteristics generated by a biomimetic swimmer - Ruoxin Li; Pengfei Wang; Yuanchuan Liu; Kai Yu; Yang Han (Ocean Engineering, 2024)

Enhancing bioretention efficiency for pollutant mitigation in stormwater runoff: Exploring ecosystem cycling dynamics amidst temporal variability - Feiwu Chen; Qian Zhang; Guangtai Zheng; Xiaojun Shen; Zhu Xue; Mucheng Zhang; Ruoxin Li; Yuan Wang (Bioresource Technology, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

X-ray diffraction and the symmetry of ultrathin crystalline materials between two-dimensional and three-dimensional crystals - Hengrui Ma; Qiaorong Jiang; Zi-Ang Nan; Gen Li; Yanyan Jia; Ruoxin Ning; Jia-Bao Ji; Zhenming Cao; Linzhe Lü; Huiqi Li; Sheng Dai; Haixin Lin; et al. (Science Bulletin, 2023)

Spatiotemporal analysis of bike mobility chain: A new perspective on mobility pattern discovery in urban bike-sharing system - Rui Xin; Jian Yang; Bo Ai; Linfang Ding; Tingting Li; Ruoxin Zhu (Journal of Transport Geography, 2023)

Type I photodynamic therapy with a self-degradable conjugated polyelectrolyte in combination with CpG adjuvant for cancer immunotherapy - Hongye Huang; Wensheng Xie; Danning Hu; Xianzhe He; Ruoxin Li; Xiaoyong Zhang; Yen Wei (Chemical Engineering Journal, 2023)

Comprehensive transcriptome analysis discovers genes related to leaf color in Cymbidium ‘Sakura’ etiolated mutant - Xiaoying Zhang; Ruoxin Ruan; Fukang Zhao; Chunnan Li; Qiaojuan Fu (Acta Physiologiae Plantarum, 2023)

Numerical Simulation of a Multi-Body System Mimicking Coupled Active and Passive Movements of Fish Swimming - Jianxin Hu; Qing Xiao; Ruoxin Li (Journal of Marine Science and Engineering, 2021)
A multi-body system model is proposed for the mimicking of swimming fish with coupled active and passive movements. The relevant algorithms of the kinematics and dynamics of the multi-body system and coupled fluid solver are developed and fully validated. A simplified three-body model is applied for the investigation of the hydrodynamic performance of both an active pitch motion and passive movement. In general, there is an optimal stiffness, under which the model swims with the fastest velocity. The effect of the damper can be drawn only when the stiffness is small. Comparing with the rigid tail, the flexible tail leads to a faster speed when the stiffness and damping coefficients are in a suitable range.